2013
DOI: 10.1007/978-1-4614-7411-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NIRS-Based Muscle Oxygenation Parameters by Inclusion of Adipose Tissue Thickness

Abstract: The assessment of muscle oxygenation by non-invasive near-infrared spectroscopy generally assumes a homogeneous medium, and this is flawed for large adipose tissue layers underneath the skin. Here we summarize the influence of the adipose tissue thickness on the oxygenation data, show that the adipose layer can be measured by NIRS and indicate a possible correction algorithm. Spectroscopic evidence suggests the usefulness of this algorithm, however, not in all subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
1
11
2
Order By: Relevance
“…1 Another plausible explanation for these divergent findings could be the fact that the correlation between ATT and totHb is significantly weaker in forearm muscles compared to leg muscles, probably due to a smaller muscle tissue thickness. 13 In contrast to the study of Grieger et al, 13 we found a significant correlation coefficient between SmO 2 and ATT in forearm muscles. These opposite results could be clarified by the fact that we measured minimal saturation values during exercise, whereas Grieger et al 13 used resting baseline values.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…1 Another plausible explanation for these divergent findings could be the fact that the correlation between ATT and totHb is significantly weaker in forearm muscles compared to leg muscles, probably due to a smaller muscle tissue thickness. 13 In contrast to the study of Grieger et al, 13 we found a significant correlation coefficient between SmO 2 and ATT in forearm muscles. These opposite results could be clarified by the fact that we measured minimal saturation values during exercise, whereas Grieger et al 13 used resting baseline values.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, no significant relation was found with totHb which is, however, in contradiction with other studies showing a significant negative relation between totHb measurements and ATT. 11,13,15 This could be due to the fact that a different NIRS technology was used in these studies, whereas CW spatially resolved spectroscopy obtains a scaled absolute value of tHb. 1 In this study FD NIRS was used, where tHb values are derived from the absolute concentration values of oxy[Hb þ Mb] and deoxy[Hb þ Mb].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Algorithms are currently being developed to account for adipose tissue thickness during SO 2 measurements with NIRS. 20 …”
Section: Discussionmentioning
confidence: 99%